1991
DOI: 10.1002/ajim.4700190104
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of inflammatory cell cytokines to disease severity in individuals with occupational inorganic dust exposure

Abstract: The pneumoconioses due to chronic occupational exposure to asbestos, coal, or silica are characterized by an alveolar macrophage-dominated alveolitis with exaggerated spontaneous release of mediators: oxidants, chemotaxins for neutrophils, and fibroblast growth factors. Bronchoalveolar lavage was performed on 66 non-smoking inorganic dust-exposed individuals with a chest x-ray greater than or equal to 1/0 stratified by presence or absence of restrictive respiratory impairment, and 28 unexposed non-smoking cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…It has been suggested that the 40% PMN level in bronchoalveolar lavage (BAL) fluid is a key level for cancer in rats. A lower, although statistically significant, increase in the percentage of PMNs has been reported in humans who were exposed to asbestos, coal, or silica and who had respiratory impairment (~4.5%, vs. 1.5% PMNs in controls) (Rom, 1991). This suggests that either the inflammation is also increased in the interstitium, or some other aspect of the inflammatory process is important, such as macrophage oxidants.…”
Section: What Are the Relevant Inflammation Parameters In Vivo?mentioning
confidence: 85%
“…It has been suggested that the 40% PMN level in bronchoalveolar lavage (BAL) fluid is a key level for cancer in rats. A lower, although statistically significant, increase in the percentage of PMNs has been reported in humans who were exposed to asbestos, coal, or silica and who had respiratory impairment (~4.5%, vs. 1.5% PMNs in controls) (Rom, 1991). This suggests that either the inflammation is also increased in the interstitium, or some other aspect of the inflammatory process is important, such as macrophage oxidants.…”
Section: What Are the Relevant Inflammation Parameters In Vivo?mentioning
confidence: 85%
“…It was shown that release of H 2 O 2 and O 2 -‱ is increased in AMs from coal workers with emphysema and pneumoconiosis (Rom, 1991(Rom, , 1990Wallaert et al, 1990). Plasma levels of lipid peroxidation end products, such as malondialdehyde, were higher in coal workers with early and low-grade CWP than in control subjects (Altin et al, 2004).…”
Section: Oxidants Cytokines and Growth Factors In Cwpmentioning
confidence: 98%
“…Fibronectin is chemotactic for fibroblasts and promotes fibroblast proliferation in vitro Bitterman et al, 1983). Further, increased production of fibronectin by AM has been demonstrated in interstitial lung diseases in humans Rom et al, 1987;Rom, 1991).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%